CLINICAL PHARMACIST INTERVENTIONS ON MILIARY KOCH’S PATIENT WITH ANTITUBERCULAR THERAPY-INDUCED HEPATOTOXICITY AND PSYCHOSIS: A RARE CASE REPORT - BANGWAL, ROHIT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Psychosis and hepatotoxicity are the dangerous side effects of the antitubercular drugs directly observed treatment short course (DOTS) therapy. Hematological spreading of tubercular bacteria in the lungs is also known as miliary tuberculosis. In this case study, 45-year-old man, weighing 55 kg was brought to the hospital with the chief complaints of vomiting (multiple episodes), fever, pain in abdomen, difficulty in breathing, mucoid cough, and disturbed sleep for the past 1 week. He had a known case of smear-positive pulmonary tuberculosis (in the past 1 month), but at that time, patient was not taking regular antitubercular treatment (ATT) medications (DOTS therapy). After 3th week of irregular antitubercular drug treatment, patient developed with the problems such as vomiting (multiple episodes), fever, pain in abdomen, difficulty in breathing, cough with expectorations, disturbed in sleep, and delirium. Pulmonologists had found the provisional and final diagnosis on the bases of subjective and objective observations miliary KOCH’S with antitubercular drugs induced hepatotoxicity and psychosis. Patients recovered from psychosis and hepatotoxicity withdrawn the first line ATT medication and tablet pyridoxine, antipsychotic medicines, and modified ATT were added in the therapy. Psychotic in a patient on ATT can be one of the complications of tablet isoniazid. As a clinical pharmacologist, we prevent and minimize drugs-induced complications and adverse drug reactions. Proper patients counseling and patients’ education are important for the better management of patients.